All things considered, my risk for diabetes is medium: A risk personalization process of familial risk for type 2 diabetes. (23rd October 2019) - Daack‐Hirsch, Sandra; Shah, Lisa L.; Jones, Kaitlyn; Rocha, Brenda; Doerr, Megan; Gabitzsch, Emily; Meese, Thad
Abstract: Background: A positive family history of type 2 diabetes (T2D) has been associated with risk awareness and risk‐reducing behaviours among the unaffected relatives. Yet, little is known about how people with a positive family history for diabetes develop and manage their personal sense of risk. Objective: To characterize two key concepts, salience and vulnerability, within the familial risk perception (FRP) model among unaffected individuals, at increased familial risk for T2D. Design: We conducted a mixed method study. Descriptions of salience and vulnerability were collected through semi‐structured interviews. Participant's perception of self‐reported risk factors (family history, age, race/ethnicity, medical history, weight and exercise) was measured using the Perceived Risk Factors for T2D Tool and was compared to a clinical evaluation of the same risk factors. Results: We identified two components of salience: (a) concern for developing T2D and (b) risk awareness triggers, and two features of vulnerability: (a) statement of risk and (b) risk assessment devices. Although few participants (26%) were concordant between their perceived and clinical overall T2D risk, concordance for individual risk factors was higher, ranging from 42% (medical history) to 90% (family history). Discussion and conclusion: Both familial and non‐familial events lead people to contemplate their T2D risk, even among people who have a positive family history. Participants often downplayed their overall risk and underestimated their overall risk compared to a clinical risk assessment of the same self‐reported risk factors. Clinicians could leverage key components of the FRP process as way to engage patients in risk reduction strategies earlier.